Left Behind, Left Unsaid: Absences On Young People’s Facebook Timelines - Robards, Brady; Lincoln, Sian (AoIR Selected Papers of Internet Research, 2017)
Since its launch in 2004, Facebook has promoted an ethos of sharing and connecting with friends. From Facebook’s motto to “connect and share with people in your life” to its recent “Friendaversary” that invites users to celebrate friendships mediated on the site, Facebook operates on a logic of sharing. While there is considerable work on sharing practices, what is less well-understood is dis-use, or the absence of disclosures. In other words, what is left unsaid on Facebook? In this paper we draw on data from the Facebook Timelines project to explore the multi-dimensional notion of ‘absence’ as it plays out on Facebook: obvious gaps, disclosures that were erased, and significant events (deaths, break-ups, failures) deemed inappropriate for Facebook. In this study we interviewed 34 people in their twenties who had been using Facebook for more than five years, in both Tasmania (Australia) and Liverpool (UK). During our interviews, we ‘scrolled back’ with our participants over their years of disclosures. This paper will be divided into three parts to cover three themes in the data: evolving social media literacies, imagined audiences, and absence on social media as a safety mechanism. We argue our findings contribute towards Light’s (2014) theorisation of ’disconnective practice’.